2020
DOI: 10.1007/s40430-020-02476-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design improvement of composite bolted π-joints under bending load

Abstract: A 3D progressive model with better convergence property is established to capture the mechanical properties and damage mechanism of a composite bolted π-joint under bending load and shown to closely match experimental results. This model is then used to investigate the effect of internal laminate stacking sequence and surface layers thickness on the bending performance of the joint. It was found that the stacking sequence and the surface layers thickness have a significant effect on the matrix crack and delami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In this investigation, the material property degradation rules for composite bolted T-joint are shown in Table 5. Cheng et al [14,15] utilized these material property degradation rules to numerically study the bending performances of composite bolted π-joint and obtained highly accurate simulation results. The corresponding user subroutine USDFLD was developed to implement the determination of element failure and material property degradation.…”
Section: Materials Damage Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this investigation, the material property degradation rules for composite bolted T-joint are shown in Table 5. Cheng et al [14,15] utilized these material property degradation rules to numerically study the bending performances of composite bolted π-joint and obtained highly accurate simulation results. The corresponding user subroutine USDFLD was developed to implement the determination of element failure and material property degradation.…”
Section: Materials Damage Modelsmentioning
confidence: 99%
“…Some studies have found that under bending loads, the primary failure mode of composite Tjoints is interlaminar delamination at the R-corner area [10][11][12][13]. Cheng et al [14,15] investigated the Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, the material property degradation rules for the composite bolted T-joint are shown in Table 5. Cheng et al [14,15] utilized these material property degradation rules to numerically study the bending performance of a composite bolted π-joint and obtained highly accurate simulation results. The corresponding user subroutine USDFLD was developed to implement the determination of element failure and material property degradation.…”
Section: Materials Damage Modelsmentioning
confidence: 99%
“…Some studies have found that under bending loads, the primary failure mode of composite T-joints is interlaminar delamination at the R-corner area [10][11][12][13]. Cheng et al [14,15] investigated the bending performance of a novel configuration composite π-joint. As shown in Figure 1, compared to the conventional π-joint [16], this novel configuration lays the warp-knitted fabric along direction 3, which converts the interlaminar load of the plies at the R-corner area into an in-plane load.…”
Section: Introductionmentioning
confidence: 99%